2018
DOI: 10.1002/art.40417
|View full text |Cite
|
Sign up to set email alerts
|

Features, Treatment, and Outcomes of Macrophage Activation Syndrome in Childhood‐Onset Systemic Lupus Erythematosus

Abstract: MAS was most likely to develop concomitantly with childhood-onset SLE diagnosis. The majority of the MAS patients were successfully treated with corticosteroids with no MAS relapses. Although the numbers were small, there was a higher risk of death associated with MAS compared to SLE without MAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 27 publications
2
59
2
2
Order By: Relevance
“…While MAS is most often associated with sJIA and AOSD, it is increasingly recognized in other rheumatologic conditions. In a recent retrospective series, close to 10% of childhoodonset SLE patients had MAS, a proportion similar to sJIA [41]. MAS has been reported in KD (1-2% of patients) but less frequently than in sJIA and SLE [42,44].…”
Section: Rheumatologicmentioning
confidence: 86%
See 2 more Smart Citations
“…While MAS is most often associated with sJIA and AOSD, it is increasingly recognized in other rheumatologic conditions. In a recent retrospective series, close to 10% of childhoodonset SLE patients had MAS, a proportion similar to sJIA [41]. MAS has been reported in KD (1-2% of patients) but less frequently than in sJIA and SLE [42,44].…”
Section: Rheumatologicmentioning
confidence: 86%
“…Preliminary SLE-specific MAS criteria have also been developed by Parodi and collaborators based on the study of 38 patients with SLE and MAS; however, this study did not have a replication cohort [105]. A recent retrospective review of a different cohort of 403 pediatric SLE patients, including 38 patients with MAS, showed that all SLE patients diagnosed with MAS by the treating physician also met the Parodi MAS criteria [41].…”
Section: Classification Criteria For Macrophage Activation Syndrome (mentioning
confidence: 99%
See 1 more Smart Citation
“…Among systemic autoimmune diseases, MAS has been described mainly in association with systemic JIA. However, it has been increasingly recognized as a complication of juvenile SLE (jSLE), with studies showing that the incidence of MAS in jSLE ranges from 5.5 to 9% [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Parodi et al [7] published preliminary diagnostic guidelines for MAS as a complication of jSLE. These guidelines were shown to be clinically relevant by Borgia et al [4], who found that all 38 patients in their study of clinically diagnosed childhood-onset SLE also met the criteria of Parodi et al [7] . Moreover, they reported that in 68% of patients, jSLE and MAS were diagnosed simultaneously.…”
Section: Introductionmentioning
confidence: 99%